2011
DOI: 10.2139/ssrn.1890569
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Laws Governing Fluctuations in Word Use from Word Birth to Word Death

Abstract: We analyze the dynamic properties of 10 7 words recorded in English, Spanish and Hebrew over the period 1800-2008 in order to gain insight into the coevolution of language and culture. We report language independent patterns useful as benchmarks for theoretical models of language evolution. A significantly decreasing (increasing) trend in the birth (death) rate of words indicates a recent shift in the selection laws governing word use. For new words, we observe a peak in the growth-rate fluctuations around 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 52 publications
5
46
0
1
Order By: Relevance
“…More specifically, they argued that some of the nonstationarity of word frequencies results from features of individuals like desires to convey information or identify with a particular social group. Petersen, Tenenbaum, Havlin, and Stanley (2012) showed that word usage varies according to social, technological, and political pressures. In the simplest case, of course people start saying words like “e-mail” once e-mail is invented; but these trends extend to, for instance, measurable differences in word frequencies and word birth and death in periods of drastic social and political change.…”
Section: Empirical Phenomena In Word Frequenciesmentioning
confidence: 99%
“…More specifically, they argued that some of the nonstationarity of word frequencies results from features of individuals like desires to convey information or identify with a particular social group. Petersen, Tenenbaum, Havlin, and Stanley (2012) showed that word usage varies according to social, technological, and political pressures. In the simplest case, of course people start saying words like “e-mail” once e-mail is invented; but these trends extend to, for instance, measurable differences in word frequencies and word birth and death in periods of drastic social and political change.…”
Section: Empirical Phenomena In Word Frequenciesmentioning
confidence: 99%
“…The competing and collaborating activities in a complex adaptive system were also studied to investigate risk-return relationships [5] and resource allocations [6] in human society. Besides, methods of statistical physics were also applied to study the birth (death) rate of words, providing an insight into the research on language evolution [7]. In the light of such directions, here we try extending some of these methods to the field of music, especially the study of notes.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, for the first time it was possible to study quantitatively aspects of cultural change as reflected in language (Michel et al, 2011;Greenfield, 2013), and rigorously assess overall vocabulary drift over the time span of two centuries (Bochkarev et al, 2014). Moreover, methods inspired in statistical mechanics of complex systems were used to study the dynamics of word birth and death (Petersen et al, 2012a), long-range fractal correlations in word frequencies over centuries (Gao et al, 2012), and the scaling behaviour of word frequencies over time as represented by Zipf's (1949) and Heaps' (1978) laws (Petersen et al, 2012b;Gerlach and Altmann, 2013).…”
Section: Introductionmentioning
confidence: 99%